2002
DOI: 10.1037/0022-3514.83.2.380
|View full text |Cite
|
Sign up to set email alerts
|

Double dissociation between implicit and explicit personality self-concept: The case of shy behavior.

Abstract: Using the trait of shyness as an example, the authors showed that (a) it is possible to reliably assess individual differences in the implicitly measured self-concept of personality that (b) are not accessible through traditional explicit self-ratings and (c) increase significantly the prediction of spontaneous behavior in realistic social situations. A total of 139 participants were observed in a shyness-inducing laboratory situation, and they completed an Implicit Association Test (IAT) and explicit self-rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

50
521
2
23

Year Published

2003
2003
2012
2012

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 576 publications
(605 citation statements)
references
References 65 publications
50
521
2
23
Order By: Relevance
“…This combination of a small correlation between the implicit and explicit measures of extraversion, and a heterotrait-monomethod correlation between two reliable IAT measures is what is expected on the basis of the reliable contamination hypothesis. However, besides interindividual differences in task-switching costs, several other factors may have contributed to the low implicit-explicit correlation obtained in Experiment 3, such as balancing of compatibility order (Asendorpf et al, 2002), and differences in the constructs tapped by implicit and explicit measures (Bosson et al, 2000;Wilson, Lindsey, & Schooler, 2000). Additionally, procedural variations like a relatively long response-stimulus interval of 800 ms and the incorporation of task-repetition trials may have played a role.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This combination of a small correlation between the implicit and explicit measures of extraversion, and a heterotrait-monomethod correlation between two reliable IAT measures is what is expected on the basis of the reliable contamination hypothesis. However, besides interindividual differences in task-switching costs, several other factors may have contributed to the low implicit-explicit correlation obtained in Experiment 3, such as balancing of compatibility order (Asendorpf et al, 2002), and differences in the constructs tapped by implicit and explicit measures (Bosson et al, 2000;Wilson, Lindsey, & Schooler, 2000). Additionally, procedural variations like a relatively long response-stimulus interval of 800 ms and the incorporation of task-repetition trials may have played a role.…”
Section: Discussionmentioning
confidence: 93%
“…Correlations above .30 have been obtained in a smaller number of studies (e.g., Asendorpf et al, 2002;Banse et al, 2001;McConnell & Leibold, 2001). …”
Section: Psychometric Propertiesmentioning
confidence: 98%
“…Past research has shown that implicit measures predict relatively automatic aspects of behavior that occur outside of conscious control, including spontaneous nonverbal behavior; in contrast, explicit measures better predict more consciously controlled behaviors, such as speech (e.g., Asendorpf, Banse, & Mücke, 2002;Dovidio et al, 2002;McConnell & Leibold, 2001). Although the current task involved the decoding rather than encoding of nonverbal signals, it nevertheless involved an on-line, dynamic perceptual judgment that required a rapid assessment of a changing stimulus.…”
Section: Discussionmentioning
confidence: 99%
“…For example, Gollwitzer et al (2007) used an IAT to assess implicit (selfrelated) aggression attitudes and found a relation between these attitudes and aggressive behavior. In this study we used two newly developed varieties of the IAT: a general IAT on bullying (similar to self-concept IATs, e.g., Asendorpf et al 2002) and a movie-primed IAT on bullying. A prime is a stimulus presented to participants preceding a test.…”
Section: The Present Studymentioning
confidence: 99%